An Analysis of Five Quran Memorization Methods in Higher Education - Abdulghani, Naser Ali; Satrial, Ardi (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2023)
Memorizing the Quran is a highly noble activity, not only bringing honor to the memorizer but also serving as a source of blessings for their parents. This activity involves the process of repeatedly reciting or listening to the Quran so that the verses become firmly embedded in memory and can be recited without referring to the mushaf. However, for students who are generally in their twenties or older, memorizing the Quran often presents particular challenges. This study aims to analyze the effectiveness of five Quran memorization methods used by students. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with five informants selected using purposive sampling. All participants were active students from three universities in West Sumatra. The results indicate that students use five methods in memorizing the Quran: i) the wahdah method, ii) the kitabah method, iii) the sima’i method, iv) the jama’ method, and v) the talaqqi method. These findings may serve as an initial reference for students who wish to begin the process of Quran memorization effectively, in accordance with their individual characteristics and abilities.